Produção de enzimas hidrolíticas por Beauveria bassiana em fermentação submersa assistida por ultrassom - Schmaltz, Silvana (2020)
The ability of the fungus Beauveria bassiana to produce hydrolytic enzymes in nutritious media has been known for many years, as well as the role of these enzymes in the fungal infectious process. This work defines a nutrient medium for the submerged production of hydrolytic enzymes (β-1,3-glucanase and chitinase) and spores of Beauveria bassiana. The use of agro-industrial products and residues was approached, showing the ability to stimulate the production of enzymes and spores. The most suitable medium for combined production was composed of rice bran (35 g.L-1), sucrose (50 g.L-1) and soybean bran (5 g.L-1), in addition to the essential minerals for growth. In order to obtain a higher production of enzymes, the application of Ultrasound (US) during the fermentation process was studied, since this technology has been increasingly used to stimulate bioprocesses. Different moments of application of US in the culture, different sonication times, as well as different application powers and work cycles were studied. In addition, multiple US treatments were tested. The best condition among those tested resulted in increases of 51% in the production of β-1,3-glucanase and 60% in the chitinase, with the application being carried out at 24 hours of cultivation with a power of 195 W, for 5 min and working cycle 0.5 s.s-¹. In order to identify possible mechanisms of action of the US on microbial biomass, SEM analyzes were performed comparing biomasses from the control culture - without sonication - with sonicated biomass in the best condition found for the application of the US. The photographs obtained allowed to identify structural differences in sonicated and non-sonicated biomass. The US was able to increase the formation of pores in the sonicated biomass, thus influencing the exchange of nutrients and products between cell and culture medium, favoring greater production and enzymatic secretion. Experiments evaluating the influence of US on nitrogen secretion by lyophilized microbial biomass were also conducted. The stimulus generated by sonication in the release of total nitrogen by biomass (47% compared to the content prior to sonication) was noticeable, in addition to an increase of 21% and 60% in the enzymatic activities of β-1,3-glucanase and chitinase, respectively, right after the application of the US. The application of US during the cultivation of Beauveria bassiana proved to be a very interesting option to increase the production and/or secretion of hydrolytic enzymes such as β-1,3-glucanase and chitinase, thus reducing the culture time.